2007
DOI: 10.1109/tcbb.2007.070202
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptive Multimeme Algorithm for Designing HIV Multidrug Therapies

Abstract: This paper proposes a period representation for modeling the multidrug HIV therapies and an Adaptive Multimeme Algorithm (AMmA) for designing the optimal therapy. The period representation offers benefits in terms of flexibility and reduction in dimensionality compared to the binary representation. The AMmA is a memetic algorithm which employs a list of three local searchers adaptively activated by an evolutionary framework. These local searchers, having different features according to the exploration logic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(51 citation statements)
references
References 56 publications
0
51
0
Order By: Relevance
“…MAs are based on a population of agents and proved to be of practical success in a variety of problem domains (Burke et al 2001;Franca et al 2001;Ishibuchi et al 2003;Ishibuchi and Narukawa 2004;Ong et al 2006;Neri et al 2007;Tang and Yao 2007;Zhou et al 2007;Boughaci et al 2009;Hasan et al 2009). …”
Section: The Proposed Methodologymentioning
confidence: 99%
“…MAs are based on a population of agents and proved to be of practical success in a variety of problem domains (Burke et al 2001;Franca et al 2001;Ishibuchi et al 2003;Ishibuchi and Narukawa 2004;Ong et al 2006;Neri et al 2007;Tang and Yao 2007;Zhou et al 2007;Boughaci et al 2009;Hasan et al 2009). …”
Section: The Proposed Methodologymentioning
confidence: 99%
“…Recent studies have shown that memetic approaches can lead to high quality solutions more efficiently than genetic algorithms (Hart William et al 2005;Ong et al 2007). MA has been successfully applied on many complex problems (Boughaci et al 2004;Burke et al 2001;Caponio et al 2007;Franca et al 2001;Ishibuchi and Narukawa 2004;Ishibuchi et al 2003;Neri et al 2007;Ong et al 2006;Tang and Yao 2007;Zhou et al 2007). The ability of MA in solving large problems motivates our choice to use memetic concepts to solve the WDP.…”
Section: The Proposed Methodologymentioning
confidence: 99%
“…Multiple LS schemes can be executed in parallel based on competition and a learning mechanism can be used to give greater chances to those efficient LS operators to be used at a later stage Ong and Keane 2004). On the other hand, multiple LS schemes can also be executed based on cooperation, where different LS operators are activated during different population evolution periods (Caponio et al 2007;Neri et al 2007). In the adaptive IO (AIO) operator that is applied in our proposed M-ACO algorithms, both BI and GI work together.…”
Section: Adaptive Inver-over Operatormentioning
confidence: 99%